Legal Protection of Protected Animals from Illegal Trade as an Effort to Maintain Environmental Conservation - ETIKA, TAKARIADINDA DIANA; RAHARJA, SUNARYA; HARTANTI; SULISTYANINGSIH, ENDANG; WIDYATAMA, YUSA PUTRA; TAMTAMA, ARGA SYA’BAN (Faculty of Law, Universitas Pekalongan, 2024)
The research entitled